2009
DOI: 10.2166/wst.2009.405
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of As(V) and As(III) by electrocoagulation using Al and Fe electrode

Abstract: A batch electrocoagulation (EC) process with bipolar electrode and potentiodynamic polarization tests with monopolar systems were investigated as methods to explore the effects of electrode materials and initial solution pH on the As(V) and As(III) removal. The results displayed that the system with Al electrode has higher reaction rate during the initial period from 0 to 25 minutes than that of Fe electrode for alkaline condition. The pH increased with the EC time because the As(V) and As(III) removal by eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Also, As(III) attached to the Al-hydroxide via outer-sphere complex in which reaction H þ ion (Eq. ( 12)) was released (Kuan et al, 2009). Danilenko et al (2005) indicated that As(III) in EC process is partially oxidized to As(V) in the case of using Al anodes.…”
Section: Arsenic Removal Mechanism With Ecmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, As(III) attached to the Al-hydroxide via outer-sphere complex in which reaction H þ ion (Eq. ( 12)) was released (Kuan et al, 2009). Danilenko et al (2005) indicated that As(III) in EC process is partially oxidized to As(V) in the case of using Al anodes.…”
Section: Arsenic Removal Mechanism With Ecmentioning
confidence: 99%
“…The sorbent surfaces such as amorphous Al(OH) 3 and Al 2 O 3 are positively charged up to pH 7 and at this pH, As(III) species (H 3 AsO 3 below pH 9.2, but H 2 AsO À 3 above pH 9.2) are uncharged and therefore cannot be bounded to the surface by electrostatic reaction. Sweep coagulation, in which interaction occurs between arsenic species and aluminium oxyhydroxide flocs such as Al(OH) 3 , AlO(OH) and Al 2 O 3 (Kuan et al, 2009;Hernandez, 2010).…”
Section: Arsenic Removal Mechanism With Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional methods for removing metals from Industrial effluents include chemical precipitation, oxidation or reduction, ion exchange, filtration, electrochemical treatment, reverse osmosis, membrane technologies and evaporation recovery (Ahluwalia and Goyal, 2007;Kuan et al, 2009;Mouedhen et al, 2009). These processes may be ineffective or extremely expensive especially when the metals in solution are in the range of 1 -100 mg l -1 (Nourbakhsh et al, 1994).…”
Section: Introductionmentioning
confidence: 99%